Crab bioturbation alters the community assemblies of abundant and rare bacteria on an intertidal wetland in the Yellow River estuary - Wang, Zhikang; Wang, Yongqi; Yang, Jisong; Yan, Junfen; Yang, Kaixin; Ren, Zhonghua; Wang, Wei; He, Yang; Li, Min; Zhan, Junfei; Guan, Bo; Wang, Xuehong; et al. (Frontiers in Microbiology, 2025)
IntroductionRevealing assembly patterns of abundant and rare bacteria is pivotal for comprehending the responses of soil bacterial community to environmental changes. Crabs exert significant impacts on soil environments through their frequent burrowing activities in intertidal wetlands. However, there remains a paucity of knowledge regarding the influencing mechanism of crab bioturbation on community assemblies of abundant and rare bacteria.MethodsWe delved into community structures, co-occurrence networks, and assembly processes of abundant and rare bacteria within crab-bioturbated soils (encompassing burrows and mounds) across an intertidal wetland.Results and discussionThe compositions and diversities of abundant and rare subcommunities were notably altered in crab-bioturbated soils. Moreover, the co-occurrence network analysis unveiled that crab bioturbation substantially modified the interaction patterns of rare bacteria, whereas its influence on abundant bacteria was comparatively minor. Furthermore, we discovered that the assembly processes of abundant subcommunities were primarily influenced by stochastic processes, while rare subcommunity assemblies were collectively shaped by both stochastic and deterministic processes. In conclusion, our study elucidates the mechanism by which crab bioturbation mediates the distinct assembly processes of abundant and rare subcommunities, and underscores the importance of considering rare bacteria when evaluating the ecological functions of intertidal wetlands.